Increased Incidence of Surgical Site Infection in IBD Patients. Issue 4 (April 2016) - Bhakta, Avinash; Tafen, Marcel; Glotzer, Owen; Ata, Ashar; Chismark, A. David; Valerian, Brian T.; Stain, Steven C.; Lee, Edward C.
Abstract : BACKGROUND: Surgical site infection is a key hospital-level patient safety indicator. All risk factors for surgical site infection are not always taken into account and adjusted for. OBJECTIVE: This study aimed to measure the impact of IBD in comparison with diverticulitis and colorectal cancer on the national rates of surgical site infection. DESIGN: The American College of Surgeons National Surgical Quality Improvement Project database was queried for all patients undergoing elective colectomy for colon cancer, diverticulitis, and IBD from 2008 through 2012. OUTCOME MEASURES: The association between surgical site infection and IBD patients was assessed. Patient demographics, rates of surgical site infection, wound class, return to operating room, and various patient characteristics were analyzed. Logistic regression was performed to determine the association with surgical site infection. RESULTS: The query yielded 71, 845 patients undergoing elective colectomy. Of these patients, 42, 132 had colon cancer, 22, 143 had diverticulitis, and 7570 had IBD. The rate of surgical site infection was 12.0% for colon cancer, 12.8% for diverticulitis, and 18.0% for IBD. Return to operating room within 30 days was 7.3% for IBD patients, 4.4% for patients with diverticulitis, and 4.9% for patients with colorectal cancer. Return to operating room within 30 days had the highest correlation to surgical site infection in both univariate and multivariable analysis. Other associative factors for surgical site infection common to both analyses included diabetes mellitus, smoking, open procedures, and obesity. LIMITATIONS: This study was limited by the data collection errors inherent to large databases, exclusion of emergent operations, and the inability to identify patients taking immunosuppressive agents. CONCLUSIONS: Patients with IBD undergoing elective colectomy have significantly increased rates of surgical site infection, specifically deep and organ/space infections. Given this information, risk adjustment models for surgical site infection may need to include IBD in their calculation.